Estudos genéticos-genômicos em Hancornia speciosa Gomes : árvore medicinal e frutífera nativa da América do Sul - Nunes, Valdinete Vieira (2021)
Hancornia speciosa is a fruit and medicinal tree native to South America. In Brazil it makes up the list of priority plants for research development. In this context, the present study aimed to i) map state of the art through articles, patents, and molecular data of the species and list perspectives for further research; ii) evaluate the fruits, seeds, and seedlings phenotypic variability, and estimate the genetic diversity in the natural population of Sergipe, aiming at conservation and genetic improvement; and iii) adopt an integrated approach of species distribution models and population genomics based on single nucleotide polymorphism (SNP) to identify areas with environmental suitability, genomic diversity and natural H. speciosa populations genetic structure. The scientific and technological production and availability of molecular data prospected in public databases. In a natural population, the fruits, seeds, and seedlings phenotypic variables were measured, and the genetic diversity was estimated by inter simple sequence repeat markers. Based on occurrence records and bioclimatic variables using distribution models, areas of greatest suitability were identified, and six natural populations were sampled, which were genotyped by sequencing in genomic diversity and structure analysis. Based on the compiled and analyzed data, Brazil is the origin country of 310 publications and 29 patents that were produced mostly by researchers with public universities. The molecular data available in public banks are sequences for the specie are nucleotides and proteins from the chloroplastid genome. In the phenotypic characterization in the native population, the fruits, seeds, and seedlings have a variation to be explored. As for the population genetic parameters, the following were obtained: He = 0.40, I = 0.50, Na = 2.0, Ne = 1.71 and 55.29% similarity. The areas with the greatest suitability (0.75 to 1.00) are the Atlantic Forest (northeastern coast) and Cerrado (central Brazil). We identified 5,046 SNPs (4,691 neutrals and 355 outliers), which allowed us to infer that there is high diversity and excess of heterozygotes in all populations and 315 private alleles. Greater genetic variation occurs within populations and there is genetic differentiation between populations in the Northeast and Midwest. For the genetic structure (neutral SNPs), three groups were formed and the population of Coxim is the most divergent. The set of outliers SNPs reveals a genetic structure formed by three groups that are correlated with the biomes in which the populations are inserted. For two outliers SNPs it was possible to identify functional annotation. The compilation and scientific, technological, and molecular information analysis carried out in this work allowed us to identify the lines of developed research, the gaps in knowledge about the specie and contribute to directing new research. The population of Sergipe showed high genetic diversity and phenotypic variability with the potential to provide propagules for the enrichment of natural populations and forest restoration. The results obtained by the combination of distribution models and population genomics contributed to advancing knowledge about the specie and developing strategies aimed at management, conservation, and genetic improvement.